Rescuing Self: Transient Isolation and Autologous Transplantation of Bone Marrow Mitigates Radiation-Induced Hematopoietic Syndrome and Mortality in Mice - Ghosh, Subhajit; Indracanti, Namita; Joshi, Jayadev; Indraganti, Prem Kumar (Frontiers in Immunology, 2017)
The inflamed bone marrow niche shortly after total body irradiation (TBI) is known to contribute to loss of haematopoietic stem cells (HSCs) in terms of their number and function. In this study, autologous-bone marrow transplantation (AL-BMT) was evaluated as a strategy for mitigating haematopoietic form of the acute radiation syndrome (hARS) by timing the collection phase (2 hours after irradiation) and reinfusion (24 hours after irradiation) using mice as a model system. Collection of bone marrow cells (BM; 0.5×106 total marrow cells) two hours after lethal TBI rescued different subclasses of haematopoietic stem and progenitor cells (HSPCs) from the detrimental inflammatory and damaging milieu in vivo. Cryopreservation of collected graft and its reinfusion 24 hours after TBI significantly rescued mice from lethal effects of irradiation (65% survival against 0% in TBI group on day 30th) and haematopoietic depression. Transient hypometabolic state (HMS) induced 2 hours after TBI effectively preserved the functional status of HSPCs and improved haematopoietic recovery even when BM was collected 8 hours after TBI. Homing studies suggested that AL-BMT yielded similar percentages for different subsets of HSPCs when compared to syngeneic bone marrow transplantation. The results suggest that the timing of collection, and reinfusion of graft is crucial for the success of AL-BMT.